Ammonium removal by metakaolin-based geopolymers from municipal and industrial wastewaters and its sequential recovery by stripping techniques - Samarina, Tatiana; Guagneli, Luca; Takaluoma, Esther; Tuomikoski, Sari; Pesonen, Janne; Laatikainen, Outi (Frontiers in Environmental Science, 2022)
A technical scheme of an ammonium recovery process from diluted municipal or industrial wastewaters was developed, and the main operational parameters of adsorption/desorption and air-stripping/acid-scrubbing or membrane units were examined. The proposed approach combines removal of ammonium nitrogen by ion-exchange mechanism on metakaolin-based geopolymers (MKGPs) followed by adsorbent regeneration. A regeneration agent was purified by air-stripping technique or membrane technology. A ready-to-use market grade fertilizer or an industrial-grade ammonia water could be obtained as the final product. The properties and regeneration ability of MKGP, prepared from activated kaolinite clay, were compared to new geopolymer adsorbents based on papermill sludge (FS MKGP). Adsorption fixed-bed column experiments with continuously circulated regeneration solution purified by air-stripping or membrane approach were conducted to determine the limits of regeneration solution’s application. Sodium and potassium salts were tested as regeneration agents, and the influence of regeneration solution composition on ammonium removal and recovery rates was investigated. Based on a breakthrough curve analysis, the removal rate of ammonium N by FS MKGP was found to be 3.2 times higher than that by MKGP for actual wastewater samples. Moreover, there were substantial differences in the regeneration regime between the two adsorbents. For air-stripping technique, a liquid-phase temperature of 45 C was minimal and enough for efficient ammonia transfer to the gaseous phase. For membrane technique, a feed-phase temperature of 40 C was enough for removing the ammonia from the regeneration solution, while no heating of a receiving phase was required.